Do Not Judge an Ossicle by Its Size: Type 1 Ossicles Associated With Posterior Tibial Tendon Dysfunction. Issue 6 (November 2020) - Gonzalez, Felix M.; Singer, Adam D.; Robertson, Douglas D.; Chamieh, Jad; Umpierrez, Monica; Labib, Sameh A.
Abstract : Introduction: Patients with type II navicular ossicles have traditionally been considered to be symptomatic, whereas patients with type I and III bones are considered asymptomatic without additional relevant imaging findings. The main objective of this study is to investigate the association of type I os naviculare with clinical symptomology and magnetic resonance imaging findings in comparison to types II and III ossicles. Methods: Three hundred nine subjects with accessory navicular bone types were identified, and their associations with focal navicular pain, pes planus alignment, ossicle or proximal navicular bone marrow edema pattern presence (BMEP), and posterior tibial tendon (PTT) sheath fluid distension were assessed. Fisher's exact test was used for categorical data and unpaired t tests for continuous data. Intraobserver and interobserver agreement was calculated. Results: Overall, 28% (85/309) of type I, 57% (176/309) of type II, and 16% (48/309) of type III accessory bones had focal navicular pain (type I vs type II, P = 0.17; type III vs type II, P = 0.001). Thirty-two percent of type I, 38% type II, and 8% type III accessory bones had pes planus (type I vs II, P = 0.3; type III vs type II, P = 0.001). Nine percent of type I, 48% of type II, and 6% of type III accessory bones had BMEP (type I vs II, P < 0.0001; type III vs type II, P = 0.001). Thirty-three percent of type I, 42% of type II, and 6% of type III accessory bones had PTT intrasheath fluid (type I vs II, P = 0.16; type III vs type II, P = 0.001). Conclusions: Symptomatic type I navicular ossicle patients demonstrate an increased tendency to present with early findings of PTT dysfunction and morphologic pes planus to a greater degree than previously recognized. Level of Clinical Evidence: 3